Primary melanoma of the nasal mucosa: Case presentation and systematic review of the literature - Lugo-Machado, Juan Antonio (2021)
Background: Mucosal melanoma represents one of the pathologies with a lower proportion among tumors of the nose and paranasal sinuses and as a consequence late diagnoses. Objective: To present the case of a male patient in the sixth decade of life with nasal mucosal melanoma and a systematic review of studies reported from 2016 to 2021. Results: The systematic search was carried out from January 2016 to December 2021 in PubMed, Google Scholar and Elsevier; 147 articles that meet the 19 criteria were located. Conclusion: The injury was prevalent in women, there was a higher prevalence in the seventh and eighth decades. The main lesions were epistaxis and nasal obstruction, involved the nasal cavity and paranasal sinuses and the left side was the most common involved. There was high frequency of advanced disease stages and distant metastases and generally with poor 5-year survival.